A double-blind, randomize, placebo-control trial to evaluate the effect of Nigella sativa on palmar arsenical keratosis patients - Bashar, Tahmina; Misbahuddin, Mir; Hossain, Md. Amir (Bangladesh Journal of Pharmacology, 2014)
This study was done to examine the role of Nigella sativa in 28 patients of palmar arsenical keratosis. Patients were randomized into two groups: Group A (n-15) receive capsules of placebo and vitamin E (200 mg) whereas Group B (n= 13) receive capsules of N. sativa oil (500 mg) and vitamin E (200 mg) orally for 8 weeks. The mean (± SD) clinical scoring of palmer arsenical keratosis in Group A before and after treatment was 99.3 ± 21.5 and 62.3 ± 14.3 respectively (37% reduction). On the other hand, in N. sativa oil treated group, the mean clinical score was 119.1 ± 20.3 before treatment which was reduced to 39.2 ± 8.4 (p<0.0001) after treatment (67% reduction). There were 65% reduction of total arsenic in nail of Group A and 30% in Group B. In conclusion, oral administration of N. sativa oil improves the symptom of palmar arsenical keratosis as a result of reduction of body arsenic load.